A new approach for identifying positional isomers of glycans cleaved from monoclonal antibodies. Issue 15 (6th July 2021) - Dyukova, Irina; Ben Faleh, Ahmed; Warnke, Stephan; Yalovenko, Natalia; Yatsyna, Vasyl; Bansal, Priyanka; Rizzo, Thomas R.
Abstract : We apply high-resolution ion mobility combined with cryogenic infrared spectroscopy to distinguish isomeric N-glycans with different terminal galactose positions. Abstract : Glycosylation patterns in monoclonal antibodies (mAbs) can vary significantly between different host cell types, and these differences may affect mAbs safety, efficacy, and immunogenicity. Recent studies have demonstrated that glycan isomers with the terminal galactose position on either the Man α1-3 arm or the Man α1-6 arm have an impact on the effector functions and dynamic structure of mAbs. The development of a robust method to distinguish positional isomers of glycans is thus critical to guarantee mAb quality. In this work, we apply high-resolution ion mobility combined with cryogenic infrared spectroscopy to distinguish isomeric glycans with different terminal galactose positions, using G1F as an example. Selective enzymatic synthesis of the G1(α1-6)F isomer allows us to assign the peaks in the arrival-time distributions and the infrared spectra to their respective isomeric forms. Moreover, we demonstrate the impact of the host cell line (CHO and HEK-293) on the IgG G1F gycan profile at the isomer level. This work illustrates the potential of our approach for glycan analysis of mAbs.